Period 8 - Crutcher, Chris (Greenwillow Books, an imprint of HarperCollinsPublishers, 2014)
Period 8 has always been a safe haven and high school senior Paulie "The Bomb" Baum a constant attendee, but as Paulie, Hannah, their friends, and a sympathetic teacher try to unravel the mystery of a missing classmate, the ultimate bully takes aim at the school.